1978
DOI: 10.1073/pnas.75.10.4940
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of phage Mu-1 integration: nalidixic acid treatment causes clustering of Mu-1-induced mutations near replication origin.

Abstract: to 1, starting from the point of origin of DNA replication to the termini of DNA replication. These results are compatible with the idea that Mu-i integrates at the replication fork.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The Tap protein regulates initiation frequency, with individual rep genes playing roles in replisome assembly and priming of DNA synthesis in both clockwise and counterclockwise directions. Early work suggested that Mu inserts preferentially near replication forks (Paolozzi et al, 1978;Fitts and Taylor, 1980). Later studies weighed against a preestablished replication fork bias (Nakai and Taylor, 1985;Sivan et al, 1988).…”
Section: A Pslt Hot Spot Linked To Dna Replicationmentioning
confidence: 99%
“…The Tap protein regulates initiation frequency, with individual rep genes playing roles in replisome assembly and priming of DNA synthesis in both clockwise and counterclockwise directions. Early work suggested that Mu inserts preferentially near replication forks (Paolozzi et al, 1978;Fitts and Taylor, 1980). Later studies weighed against a preestablished replication fork bias (Nakai and Taylor, 1985;Sivan et al, 1988).…”
Section: A Pslt Hot Spot Linked To Dna Replicationmentioning
confidence: 99%
“…Secondary transpositions to many different sites also occur, as is reflected by the variability of host sequences at both ends of the viral DNA (3,4). The ability of Mu DNA to integrate into many sites led to the hypothesis that it is inserted preferentially at chromosome replication forks (9,21,22). The hypothesis of preference for replication forks for lysogenic integrations was supported by the frequencies of gene inactivation in nalidixic acid-treated cells (22) and by sequential inactivation of genes in synchronized cultures infected at intervals (21).…”
mentioning
confidence: 99%
“…The ability of Mu DNA to integrate into many sites led to the hypothesis that it is inserted preferentially at chromosome replication forks (9,21,22). The hypothesis of preference for replication forks for lysogenic integrations was supported by the frequencies of gene inactivation in nalidixic acid-treated cells (22) and by sequential inactivation of genes in synchronized cultures infected at intervals (21). Comparative kinetics of zygotic induction of synchronized, Mu-infected Hfr strains indicated that in a lytic pathway as well, at least the earlier transpositions occur preferentially at replication forks (9).…”
mentioning
confidence: 99%
“…Along with earlier observations on transposition from nonreplicating bacteriophage genomes (5), these experiments indicated that replication of donor replicons was not essential for transposable element DNA rearrangements. On the other hand, studies of the specificity of bacteriophage Mu insertion into the E. coli chromosome suggested a particular affinity for the replication fork and, consequently, a possible recombinational role of the target molecule's replication mechanism (6,7). In order to study this possibility further, we examined the effect on Tnl -specific replicative recombination of blocking target replicon duplication.…”
mentioning
confidence: 99%